2011
DOI: 10.1371/journal.ppat.1002321
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Predicted HIV-1 Replicative Capacity in a Clinical Setting

Abstract: HIV-1 replicative capacity (RC) provides a measure of within-host fitness and is determined in the context of phenotypic drug resistance testing. However it is unclear how these in-vitro measurements relate to in-vivo processes. Here we assess RCs in a clinical setting by combining a previously published machine-learning tool, which predicts RC values from partial pol sequences with genotypic and clinical data from the Swiss HIV Cohort Study. The machine-learning tool is based on a training set consisting of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 19 publications
0
64
0
Order By: Relevance
“…CTL escape mutations may be reverted if the virus harbouring a costly CTL-escape mutation is transmitted to an individual where the mutation does not help evade the new host’s immune system (Carlson et al, 2014; Zanini et al, 2015). Mutations that increase the replicative capacity of the virus in all hosts may also evolve (Kouyos et al, 2011). It is also a possibility that slightly deleterious or beneficial mutations get fixed by genetic drift.…”
Section: Resultsmentioning
confidence: 99%
“…CTL escape mutations may be reverted if the virus harbouring a costly CTL-escape mutation is transmitted to an individual where the mutation does not help evade the new host’s immune system (Carlson et al, 2014; Zanini et al, 2015). Mutations that increase the replicative capacity of the virus in all hosts may also evolve (Kouyos et al, 2011). It is also a possibility that slightly deleterious or beneficial mutations get fixed by genetic drift.…”
Section: Resultsmentioning
confidence: 99%
“…2,8 It has been shown that the virulence and the replicative capacity of the virus are highly correlated. 9 Therefore, viral set point during the asymptomatic stage of the disease has been used as a proxy for virulence of the HIV virus. 10 An individual with a high (low) viral load is most probably infected with a strain of HIV-1 that has a high (low) replicative capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Small virus-derived peptides called epitopes are presented on the surface of infected cells by the human leukocyte antigen (HLA) class 1 molecules, which then allows CTLs to recognize and kill these cells. Throughout the course of chronic infection, which may last from a few years to a decade, viral diversity and fitness gradually increase [17,72,73]. Antigenic diversity also increases, as HIV continuously generates escape mutations in CTL epitopes, preventing them from being presented or recognized [63,72,[74][75][76].…”
Section: Hiv Pathogenesis Involves Immune-directed Evolutionmentioning
confidence: 99%